Materials toward an edition of William Camden's Remains concerning Britain - Dunn, R; Dunn, Robert D. (1972)
﻿ This thesis represents the first stage of a projected complete edition of Camden's Remains. I offer here Camden's text for three chapters (Britain, Inhabitants, and the Wise Speeches) along with a textual apparatus. The General and Textual Introductions are based on a study of the whole book. The General Introduction examines the relation of the Remains to Camden's major work, the Britannia. It also contains a discussion of Camden's sources and the manner in which he handles his material. Briefly, I indicate the extent of Camden's contact with other historians and antiquarians and state whose libraries he had access to. Discussion is purposely brief because these and related matters have already been: treated in works by Linda van Norden, F. T. Levy, and May McKisack. A separate study of how and where Camden saw the manuscripts and books he used lies outside the scope of the thesis. To conclude the General Introduction I offer brief comments on Camden's style, his intentions, and the place of the Remains in relation to his two historical works. The Textual Introduction studies the evidence of the manuscripts and of the three editions in Camden's lifetime. The text is based on the edition of 1605. It adopts the authoritative revisions and additions of 1614 and 1623. The apparatus at the bottom of each page records substantive variants of the manuscripts, 1614, and 1623. It also records all departures from the copy text. Commentary for the two sections Britain and Inhabitants is confined to identifying sources and explaining points in the text. For the Wise Speeches, I attempt to trace the origin and development of each story and, where possible, to identify Camden's source or the tradition leading to Camden's version. In a number of cases it is possible to identify the particular manuscript or edition which Camden used and these have been noted. I indicate any changes Camden has made in the substance of a story and, in most cases, I present for comparison the text of the speech or aphorism. The Commentary was designed for the convenience of the general reader, hence some entries are no doubt fuller than an historian would need. Appendix A presents a selection of manuscript apophthegms which, for one reason or another, Camden chose not to print. They are not part of his final intentions. For this and other reasons, I offer them here, unannotated, simply as a sample of the contents of the manuscript. I hope to deal with the unpublished apophthegms separately at another time. Appendix B provides a table identifying all the material Camden added to the editions of 1614 and 1623.